Report of the Activities Completed During Sabbatical Leave in the Fall of 2007. - Schmitt, Elena (Distribution: Fall 2007 ; World Languages and Literatures., 2007)
Research completed during this leave focused on the already collected data for an article outlining distinctions between language attrition and incomplete acquisition, and on a new project and new data for research on how literacy or its lack in a minority language affects the degree of language maintenance and development.
Keywords: dept.wll; faculty_collection; sabbatical_report